Disaster Risk Reduction - Trohanis, Zoe; Dastur, Arish; Xu, Ting; Cira, Dean (World Bank, Washington, DC, 2012)
In order to address the impact of the Wenchuan earthquake, which occurred on 12 May 2008 and registered 8.0 on the Richter scale, the Government of China will implement an effective, comprehensive, and sustainable recovery program. At the same time, it is important that the government consider how the recovery process can contribute to disaster risk reduction (DRR), the objective being to make communities and assets significantly more resilient to the impact of future disasters. A primary aim of recovery management is to use the opportunity to build or strengthen resilience in society that is, its citizens, livelihoods, buildings, critical facilities, government administration, and the natural environment. To establish an effective DRR framework, key institutional actors and stakeholders need to work together and be aware of their respective roles and responsibilities. These include the national, provincial, and local government levels, the relevant government ministries and agencies, and local communities. An effective disaster management system covers the following five aspects: (i) risk identification; (ii) emergency preparedness; (iii) institutional capacity building; (iv) risk mitigation; and (v) catastrophe risk financing.